If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + -8x = 9x + 21 Reorder the terms: -13 + -8x = 21 + 9x Solving -13 + -8x = 21 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -13 + -8x + -9x = 21 + 9x + -9x Combine like terms: -8x + -9x = -17x -13 + -17x = 21 + 9x + -9x Combine like terms: 9x + -9x = 0 -13 + -17x = 21 + 0 -13 + -17x = 21 Add '13' to each side of the equation. -13 + 13 + -17x = 21 + 13 Combine like terms: -13 + 13 = 0 0 + -17x = 21 + 13 -17x = 21 + 13 Combine like terms: 21 + 13 = 34 -17x = 34 Divide each side by '-17'. x = -2 Simplifying x = -2
| 5x+9=-1 | | -4+w=5 | | 7x+4-x=40 | | 6x+12=-27-7x | | 7-2x=-13 | | 162-6x=4x+12 | | y=x^2+6x-10 | | -9+3x=12 | | 13=-4+t | | 8=3x^2+x | | 5(7-3t)=21t+35 | | 2x+9=89-6X | | 10+7x-2x=65 | | 7+7x=61+x | | 2y=x-10 | | 0.2(x+3)=1.4 | | -4x-5=31 | | 2x+29=4x+11 | | 12x-20=112 | | -4x=-6 | | 5x+8=33 | | 7x-y=30+4y | | 6x+16=13x-47 | | -8x+9y=77 | | 24+5x=4(6+2x)-3x | | (4x+3)(x+4)-(x-1)(x-3)=3x(x-2) | | 36=-19(y+8) | | -4[2x-3(3x+4)]+5x=-17 | | x-5=15*5 | | 46=-20(y+9) | | x^2-48=2x | | 106-2x=25x+22 |